BEEF CATTLE BUSINESS RESOURCES AND LAND TENURE: CATTLE BUSINESS PERFORMANCE INCOME FARMERS CONTRIBUTION - Rahmi Wahyuni (Widyariset, 2015)
Integrated farming is an alternative effort in order to improve business efficiency in beef cattle farming land.The extent to which it can flourish and contribute to is an exciting thing to assess. Research conducted at the centerof beef cattle in Nagari Sungai Kamuyang, Subdistrict Luak, District Lima Puluh Kota, West Sumatra in 2013.The aim is to analyze the relationship mastery of agricultural resources (land) with cattle control, and its impacton business performance of livestock and household income structure of farmers, survey collection methods, datacollection using structured questionnaires and in-depth interviews. Determination of the respondents conducted by purposive sampling involved 30 farmers. Data were analyzed by descriptive quantitative and qualitative and presented in tabular form as well as a SWOT analysis. The results showed: (a) The relationship between the area of agricultural land ownership by the number of cattle is that the more the number of farms ownership increasing numbers of livestock . Land tenure of >0.5 ha has five cattles. (b) Contribution of the cattle business in research area with agricultural land <0.5 ha is <35 % of total farm household income. (c) Contribution of the cattle business with land holdings >0.5 ha is >40% of total farm household income. Profits per three cows Rp2,786,500.00/periode. R/C = 1.129. This means cattle business is well worth the effort. B/C = 0.129 profits earned is 12.9% of the costs incurred. (d) Priority beef cattle business development strategy is cooperation with other agencies in thedevelopment of feed by utilizing the available land, the provision of knowledge and technology to farmers in order to develop the cattle business, collaboration with agencies planter capital.